STUDI EKSPERIMENTAL PENGARUH TEMBAGA TERHADAP KUAT TARIK BAJA - Muhammad Jailani Muslim; Ageng Habrur Fahmi; Purwanto Purwanto; Arif Hidayat (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Steel is a metal alloy composed of iron as main element and carbon as an element of reinforcement. Carbon element play a role in improving the quality of the steel. Combined steel to can fix the ability of tensile strength the steel. In this research, combine carbon steel with copper. Copper alloy steel expected to increase the tensile strength of the steel. In this research we use sample with the non alloy steel (TP), alloy steel with 0,5% copper alloy (FeCu-5), and alloy steel with 1,0% copper alloy (FeCu-10), testing that will do in the form of composition testing, hardness testing, and tensile testing. The steel tensile testing we get the data of stress,strain,modulus elasticity,and ductility. The result obtaine from this research is 1% copper alloy increases the ultimate tension by 42,42% compared with non alloy steel. While there is decrease in the ultimate strees by 0,5% copper alloy by 30,98% compared with non alloy steel.